TG13 miscellaneous etiology of cholangitis and cholecystitis - Higuchi, Ryota; Takada, Tadahiro; Strasberg, Steven M.; Pitt, Henry A.; Gouma, Dirk J.; Garden, O. James; Büchler, Markus W.; Windsor, John A.; Mayumi, Toshihiko; Yoshida, Masahiro; Miura, Fumihiko; Kimura, Yasutoshi; et al. (Journal of hepato-biliary pancreatic sciences, 2013)
This paper describes typical diseases and morbidities classified in the category of miscellaneous etiology of cholangitis and cholecystitis. The paper also comments on the evidence presented in the Tokyo Guidelines for the management of acute cholangitis and cholecystitis (TG 07) published in 2007 and the evidence reported subsequently, as well as miscellaneous etiology that has not so far been touched on. (1) Oriental cholangitis is the type of cholangitis that occurs following intrahepatic stones and is frequently referred to as an endemic disease in Southeast Asian regions. The characteristics and diagnosis of oriental cholangitis are also commented on. (2) TG 07 recommended percutaneous transhepatic biliary drainage in patients with cholestasis (many of the patients have obstructive jaundice or acute cholangitis and present clinical signs due to hilar biliary stenosis or obstruction). However, the usefulness of endoscopic naso-biliary drainage has increased along with the spread of endoscopic biliary drainage procedures. (3) As for biliary tract infections in patients who underwent biliary tract surgery, the incidence rate of cholangitis after reconstruction of the biliary tract and liver transplantation is presented. (4) As for primary sclerosing cholangitis, the frequency, age of predilection and the rate of combination of inflammatory enteropathy and biliary tract cancer are presented. (5) In the case of acalculous cholecystitis, the frequency of occurrence, causative factors and complications as well as the frequency of gangrenous cholecystitis, gallbladder perforation and diagnostic accuracy are included in the updated Tokyo Guidelines 2013 (TG13).
Gesehen am 10.05.2021